(untitled) (Perner’s Contacts, 2014)
The paper deals with the essence of the problem of queuing and its possible capacity planning using the various dimensions of capacity. Includes monitoring key indicators of good general application and efficiency of utilization of transport undertakings to detect formation of operational problems. The paper presents a part of the output, the data processing carried out research dealing with the after-sales phase for the area of complaints. The results are listed in descending order of importance weights, which customers said for various quality criteria. The paper contains a graphical representation of the impact of provider quality management service in the customer’s decision-making under conditions of liberalized market.